2014
DOI: 10.3389/fimmu.2014.00433
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles in Modulating the Host Immune Response during Parasitic Infections

Abstract: Parasites are the cause of major diseases affecting billions of people. As the inflictions caused by these parasites affect mainly developing countries, they are considered as neglected diseases. These parasitic infections are often chronic and lead to significant immunomodulation of the host immune response by the parasite, which could benefit both the parasite and the host and are the result of millions of years of co-evolution. The description of parasite extracellular vesicles (EVs) in protozoa and helmint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 67 publications
5
67
0
2
Order By: Relevance
“…Many reports Montaner et al 2014) have shown the diversity of proteins included in exosomes and microvesicles through proteomic analysis and have been included at the Evpedia (Kim et al 2015).…”
Section: Content Of Biomoleculesmentioning
confidence: 99%
“…Many reports Montaner et al 2014) have shown the diversity of proteins included in exosomes and microvesicles through proteomic analysis and have been included at the Evpedia (Kim et al 2015).…”
Section: Content Of Biomoleculesmentioning
confidence: 99%
“…A proteomic analysis of extracellular vesicles released by metacyclic trypomastigotes and epimastigotes in culture demonstrated the presence of two populations of EVs containing plasma membrane and intracellular proteins, and also nucleic acids (26,29,(32)(33)(34). Interestingly, treatment of mice with EVs shed by axenic trypomastigotes caused a downmodulation of the host immune response that was associated with higher parasitemia and an exacerbated inflammatory response that resulted in increased mortality following infection (26,35). The T. cruzi small membrane proteins (TcSMP) family of proteins or phosphatases detected on T. cruzi EVs has been shown to trigger Ca 2ϩ signaling and lysosome mobilization/exocytosis, events that promote formation of parasitophorous vacuoles and parasite invasion (36,37).…”
mentioning
confidence: 99%
“…is. Similar to host and parasites, EVs could also facilitate signaling between the Plasmodium parasite and the mosquito vector (Deolindo et al, 2013;Twu et al, 2013;Bayer-Santos et al, 2014;Montaner et al, 2014). This information exchange is likely to have played a key role in the initial approach between host and parasite that ended up in the establishment of the infection (Figure 1D).…”
Section: Evolutionary Consequences Of Interkingdom Communicationmentioning
confidence: 99%